EFESIENSI BIAYA DISTRIBUSI DENGAN JARAK DAN WAKTU TEMPUH TERHADAP KAPASITAS GUDANG - Sumiyanto Sumiyanto Sumiyanto (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
ABC is a system integrator company engaged in the field of information technology in Jakarta. ABC company is provides information technology solutions to customers in the form of hardware and software. ABC’s company must be have a proper distribution system in distributing products. On this basis, an efficient of distribution process analysis in minimizing the cost of distribution of goods with the right delivery time. Analytical Hierarchy Process (AHP) is used to determine the distribution area based on criteria determined in an effort to maximize warehouse capacity. Procurement of information technology tools can minimize distribution costs by 27.79%. Thus, the cost of distributing information technology devices is more efficient. Kata kunci: System integrator, information technology, Analytical Hierarchy Process (AHP)